The Plecoptera collection at the Natural History Museum in Oslo - Boumans, Louis (Illiesia, 2011)
The Natural History Museum, University of Oslo (NHM) houses a very large ethanol collection of Norwegian stoneflies. About half of this material is sorted and labelled; the other half consists of unsorted and largely unidentified samples. In addition, there are some 5000 high quality microscopeslides of nymphal and adult body parts. Most samples were collected by the late Albert Lillehammer (1930-1992). In 2010 the collection built by Lillehammer has been digitized and georeferenced. 4305 specimen-based records have been made accessible online through the data portals of Artskart, a web service of the Norwegian Biodiversity Information Centre Artsdatabanken, and the Global Biodiversity Information Facility (GBIF). In order to facilitate access and future use, the Plecoptera collection at the NHM is described, with comments on the less common Norwegian species. The slide-mounted epiproctsof the males of the Arctic species Nemoura arctica Esben-Petersen 1910, N. sahlbergi Morton 1896 and N. viki Lillehammer 1972 are depicted. The paper concludes with suggestions for future applications of the NHM's stonefly collection.
Keywords: entomology; vrbnice; collections; entomologija; Plecoptera; muzejske zbirke; Nemoura; epiproct; Lillehammer; Norway